2000
DOI: 10.1046/j.1365-2621.2000.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the single cell gel electrophoresis assay (Comet assay) as a technique for monitoring low-temperature treated and irradiated muscle tissues

Abstract: The influence of refrigeration, freezing, repetitive freezing-thawing, and irradiation on meat quality were evaluated by detecting DNA damage to beef muscle tissues using the single cell gel electrophoresis assay (Comet assay). Comet tail lengths indicating DNA damage levels increased with refrigeration time up to 10 days. In the case of frozen storage, the damage was increased only for the first 15 days of storage, but after that, decreased slightly and the tail lengths at 15 days were similar to those of 3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…2, these conditions also led to an increase in the slope of the corresponding standard curve from À3.4 for the dough that had not been frozen to À 4.1, resulting in a decrease of the amplification efficiency from 97% to 75%. Park et al (2000) showed that DNA from meat samples is damaged after 15 days of storage at À20 C. The observed effect can therefore be explained by DNA degradation caused by freezing and subsequent thawing. Detection of lupine DNA was still possible at 0.1 mg/kg with a mean Ct value of 38.4, whereas no amplification was observed in the reactions performed on the 0.01 mg/kg sample and the blank sample.…”
Section: Concentrationmentioning
confidence: 98%
“…2, these conditions also led to an increase in the slope of the corresponding standard curve from À3.4 for the dough that had not been frozen to À 4.1, resulting in a decrease of the amplification efficiency from 97% to 75%. Park et al (2000) showed that DNA from meat samples is damaged after 15 days of storage at À20 C. The observed effect can therefore be explained by DNA degradation caused by freezing and subsequent thawing. Detection of lupine DNA was still possible at 0.1 mg/kg with a mean Ct value of 38.4, whereas no amplification was observed in the reactions performed on the 0.01 mg/kg sample and the blank sample.…”
Section: Concentrationmentioning
confidence: 98%
“…Methods such as thermoluminescence and pulsed photostimulated luminescence are useful for the detection of fresh and dry food items that contain silicate minerals 2–12. Foods of plant or animal origin that are irradiated to low dose levels can be monitored using the DNA comet assay 13–20. Electron paramagnetic resonance (EPR) or electron spin resonance (ESR) is a well‐established method based on the free radicals that are produced upon irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…DNA Comet assay provides an inexpensive, rapid, convenient, simple, qualitative and to some extent quantitative method for the irradiation detection of varieties of foods, which are exposed to even low radiation absorbed doses. This assay has increasingly been recognized as a valuable tool for regulatory studies (Koppen and Cerda 1996;Delincee 1998;Park et al 2000;Villavicencio et al 2000Villavicencio et al , 2004Khan et al 2002a;Huachaca et al 2005;Kumaravel and Jha Awadhesh 2006;Cutrubinis et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA Comet assay technique was applied for the first time on food stuff to measure qualitative as well as quantitative DNA damage in single cell (Cerda et al 1997). It is now widely used in a variety of research areas such as radiation biology, genetic toxicology and cancer research (Fairbairn et al 1995;Cerda et al 1997;Park et al 2000).…”
Section: Introductionmentioning
confidence: 99%